2017
DOI: 10.5194/isprs-annals-iv-4-w5-125-2017
|View full text |Cite
|
Sign up to set email alerts
|

User Requirements Gathering for 3d Geographic Information in the United Kingdom

Abstract: ABSTRACT:Despite significant developments, 3D technologies are still not fully exploited in practice due to the lack of awareness as well as the lack of understanding of who the users of 3D will be and what the user requirements are. From a National Mapping & Cadastral Agency and data acquisition perspective, each new 3D feature type and element within a feature added (such as doors, windows, chimneys, street lights) requires additional processing and cost to create. There is therefore a need to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Several studies have conducted different forms of requirements analysis of 3D data (Biljecki et al, 2015;Sargent et al, 2015;Stoter et al, 2013;Stoter et al, 2016;Walter, 2014;Wong and Ellul, 2017) -more details on these studies can be found in Wong and Ellul (2017). Two key points emerge from these studies.…”
Section: D Data Requirements Gatheringmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have conducted different forms of requirements analysis of 3D data (Biljecki et al, 2015;Sargent et al, 2015;Stoter et al, 2013;Stoter et al, 2016;Walter, 2014;Wong and Ellul, 2017) -more details on these studies can be found in Wong and Ellul (2017). Two key points emerge from these studies.…”
Section: D Data Requirements Gatheringmentioning
confidence: 99%
“…In summary, it is therefore important to explore user requirements for 3D GI at the application-specific and the country-specific level, to allow NMCAs and other data producers to prioritise work towards the needs of the national audience. Within the context of the UK, a study by Wong and Ellul (2017) explored user requirements gathering for 3D geographic information using qualitative methods. Web-based questionnaires and semi-structured face-to-face interviews were used to assess the state of 3D GI adoption and use within the UK.…”
Section: D Data Requirements Gatheringmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, user-centered approaches involve users in every step of a design, e.g., the design of an information system [35]. Such a design process includes context analysis, defining user requirements, designing solutions, and evaluation [36,37]. Putting users at the centre should ultimately reduce the digital divide and bridge communications gaps between local users and EO-researchers [19].…”
Section: Introductionmentioning
confidence: 99%